ANALISIS KEPUASAN KONSUMEN TERHADAP PENGGUNAAN MARGARIN MEREK BLUE BAND (Studi Kasus: Aroma Prima Supermarket Kec. Medan Johor, Sumatera Utara) - Nasution, Muhammad Arif (Agriprimatech, 2024)
The aim of this research is to identify the level of consumer satisfaction with the use of Blue Band brand margarine and the characteristics of consumers of Blue Band brand margarine. Sampling was carried out using the Slovin formula with a sample of 95 respondents. The data analysis methods used are the Importance Performance Analysis (IPA) and Customer Satisfaction Index (CSI) methods. Data processing was assisted with Microsoft Excel 2010 and SPSS version 25. This research was conducted in March-April 2023. The results of this research concluded that the results of the Importance Performance Analysis (IPA) analysis of the blue band brand margarine product variables were classified into 4 quadrants, namely: quadrants I is considered the main priority in the form of: ease of obtaining. Quadrant II is considered to be achievements in the form of: branding, attractive packaging, melting quickly, making delicious dishes, advertising and promotion, widely used by people and delicious aroma. Quadrant III is considered low levels in the form of: product size variations, affordable prices, expiry dates, usability of various food products, nutritional information and halal guarantees, information services and pride in using. Quadrant IV contains no variables in the quadrant. The results of the Customer Satisfaction Index (CSI) analysis obtained a value of 68.61% which is in the scale range of 60% <CSI≤ 80%. This shows that respondents of the Blue Band brand margarine are included in the satisfaction criteria.